In Vitro Evaluation of Electrospun Silk fibroin Scaffolds for Vascular Cell Growth - Zhang, Xiaohui (2008)
Human aortic endothelial (HAEC) and human coronary artery smooth muscle cell (HCASMC) responses on electrospun silk fibroin scaffolds were studied to evaluate potential for vascular tissue engineering. Cell proliferation studies supported the utility of this biomaterial matrix by both HAECs and HCASMCs. Alignment and elongation of HCASMCs on random nonwoven nanofibrous silk scaffolds was observed within 5 days after seeding based on SEM and confocal microscopy. Short cord-like structures formed from HAECs on the scaffolds by day 4, and a complex interconnecting network of capillary tubes with identifiable lumens was demonstrated by day 7. The preservation of cell phenotype on the silk fibroin scaffolds was confirmed by the presence of cell-specific markers, including CD146, VE-Cadherin, PECAM-1 and vWF for HAECs, and SM-MHC(2) and SM-actin for HCASMCs at both protein and transcription levels using immunocytochemistry and real time RT-PCR, respectively. Formation of ECM was also demonstrated for the HCASMCs, based on the quantification of collagen type I expression at protein and transcription levels. The results indicate a favorable interaction between vascular cells and electrospun silk fibroin scaffolds. When these results are factored into the useful mechanical properties and slow degradability of this protein biomaterial matrix, potential utility in tissue-engineered blood vessels can be envisioned.